RuBisCO as a protein source for potential food applications: A review. (1st September 2023) - Grácio, Madalena; Oliveira, Sabrina; Lima, Ana; Boavida Ferreira, Ricardo
Highlights: RuBisCO is an abundant plant-based, non-allergenic and readily digested protein. RuBisCO has a composition approaching that of the ideal protein as defined by FAO. RuBisCO has excellent functional properties and is precursor to many bioactive peptides. Existing cost-effective, large-scale RuBisCO purification methods present serious drawbacks. Due to its unique features, development of methods for RuBisCO large-scale isolation is awaited. Abstract: RuBisCO is a complete protein, widely abundant and recognized as ideal for human consumption. Further, its biochemical composition, organoleptic and physical features mean RuBisCO has potential as a nutritionally beneficial food additive. Nonetheless, despite growing plant-based market trends, there is a lack of information about the applications of this protein. Here, we explored the biochemical features of RuBisCO as a potential food additive and compared it with other plant protein sources currently available. We describe potential advantages, including nutritional content, digestibility, non-allergenicity and, potential bioactivities. Despite the lack of industrial procedures for RuBisCO purification, a growing number of novel methods are emerging, justifying discussion of their feasibilities. Overall, this information can help both researchers and industry to review the use RuBisCO as a sustainable source of protein for plant-based food products or formulation of novel functional foods.